Excessive salt consumption causes systemic calcium mishandling and worsens microarchitecture and strength of long bones in rats - Wacharaporn Tiyasatkulkovit (2022)
Excessive salt intake has been associated with the development of non-communicable diseases, including hypertension with several cardiovascular consequences. Although the detrimental effects of high salt on the skeleton have been reported, longitudinal assessment of calcium balance together with changes in bone microarchitecture and strength under salt loading has not been fully demonstrated. To address these unanswered issues, male Sprague–Dawley rats were fed normal salt diet (NSD; 0.8% NaCl) or high salt diet (HSD; 8% NaCl) for 5 months. Elevation of blood pressure, cardiac hypertrophy and glomerular deterioration were observed in HSD, thus validating the model. The balance studies were performed to monitor calcium input and output upon HSD challenge. The HSD-induced increase in calcium losses in urine and feces together with reduced fractional calcium absorption led to a decrease in calcium retention. With these calcium imbalances, we therefore examined microstructural changes of long bones of the hind limbs. Using the synchrotron radiation x-ray tomographic microscopy, we showed that trabecular structure of tibia and femur of HSD displayed a marked increase in porosity. Consistently, the volumetric micro-computed tomography also demonstrated a significant decrease in trabecular bone mineral density with expansion of endosteal perimeter in the tibia. Interestingly, bone histomorphometric analyses indicated that salt loading caused an increase in osteoclast number together with decreases in osteoblast number and osteoid volume. This uncoupling process of bone remodeling in HSD might underlie an accelerated bone loss and bone structural changes. In conclusion, long-term excessive salt consumption leads to impairment of skeletal mass and integrity possibly through negative calcium balance.